“We Weren’t Taught How to Recover from a Pandemic:” Recent Occupational Therapy Graduates’ Reflections on COVID-19 - Laura H. VanPuymbrouck; Carli Friedman (Journal of Occupational Therapy Education, 2022)
In the spring of 2020, graduates from occupational therapy (OT) programs across the globe were entering a world of clinical unknowns. The students from this graduating cohort likely had little to no education or training on how to deliver OT in the wake of COVID-19. How well prepared did these new graduates perceive themselves to be to enter a healthcare climate in a pandemic and what were their biggest concerns? The objective of this study was to understand new graduates’ perspectives of the impact of COVID-19 on their future as occupational therapy practitioners (OTPs), and their sense of preparedness to address the challenges they might face. To do so, nine recent OT graduate students participated in semi-structured individual interviews. First cycle data analysis used descriptive and in-vivo codes and second cycle coding used pattern coding to identify emergent themes from across interviews. Three themes emerged in data analysis that represented how participants saw COVID-19 impacting their lives and their role as OTPs on multiple levels of systems and practice. These themes are: 1) Micro: COVID-19’s impact on work with clients; 2) Meso: COVID-19’s impact on the profession and the provision of OT; and 3) Macro: COVID-19’s impact on systems and structures. Based on these findings, implications for educators moving forward include: methods for preparing students to work with clients virtually and in a post-pandemic world; recommendations for developing strategies for working in unpredictable and unknown contexts; and, suggestions for addressing issues of equity and social justice.